Performance determinants of Hong Kong’s Banking Industry - Wong, Nok-Him (2016)
Hong Kong is well known as an international financial centre meanwhile the banking sector has been growing rapidly since the beginning of the 21st century. As the industry contributes more to the GDP within the city, it becomes necessary to monitor the performances of banks so as to maintain stability of the overall economy. This paper has used a dynamic SGMM model to evaluate the performance of the top 20 commercial banks in Hong Kong while indicating the determinants that influences the most on their profitability, with regards of the growing importance of the non-interest activities. In the meantime, with raising awareness to the service quality of banks nowadays, the paper has been going through a discussion on the topic while indicating the importance and relationship between the interactions with customers and their loyalty. Finally, challenges and opportunities are also discussed at the end of the paper, competitions coming from China that disrupts Hong Kong banks’ profitability and the transformation of Hong Kong into a fintech hub that offers potential growth for the banking industry are concluded as major concerns in banks’ performances in the future.